Method for testing service life of hot-pressing sealing assembly for sodium salt battery
By placing the heat -sealing component in the high temperature corrosion environment of sodium aluminate for multiple freezing and fusion treatment, simulated the battery service environment, solve the problem of low accuracy of existing test methods and complicated procedures, and achieve more accurate accurate Performance tests and battery life improvement.
Patent Information
- Application Number
- CN202411331393.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-21
AI Technical Summary
The existing hot press sealing component testing methods have problems such as low testing accuracy and complicated testing procedures, which cannot effectively reflect the performance status of the components in high-temperature corrosion environments.
The life test method of a hot pressure seal component of sodium salt batteries is designed. By placing the heat pressure sealing component in a high -temperature corrosion environment composed of sodium aluminate, multiple freezing and melting treatment is performed to simulate the battery service to serve in service. The mechanics recession in the environment is judged by the inspection and tensile strength test.
The accuracy of testing is improved, and the test process process is simplified, which can more accurately reflect the performance state of the thermal pressure seal component in the high temperature corrosion environment, thereby improving the life and quality of the battery.
Smart Images

Figure CN119334549A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium salt battery testing, and in particular relates to a life testing method for a hot pressing sealing component for a sodium salt battery. Background Art
[0002] Sodium-nickel batteries and sodium-sulfur batteries are both high-temperature energy storage batteries. As the seals that isolate the positive and negative electrodes of the battery, the hot-pressed sealing components need to have ideal sealing strength and airtightness under the long-term high-temperature NaAlCl4 vapor corrosion. Through the hot-hot cycle accelerated corrosion test of the hot-pressed sealing components immersed in liquid NaAlCl4, it is found that while the hot-pressed sealing components are accelerated to corrode by the NaAlCl4 melt at high temperature, stress will also be generated in the sealing area during the solid-liquid transformation of NaAlCl4.
[0003] The current heat-pressed sealing components are made of metallized ceramics and nickel rings, such as Figure 1 As shown, the performance of the hot press sealing assembly is usually judged by evaluating the sealing strength of the ceramic metallization layer combined with the nickel ring to ensure its reliability and safety in practical applications.
[0004] The existing traditional method of testing the performance of hot-pressed sealed components usually includes testing its mechanical properties, sealing, temperature performance and corrosion resistance, and then comprehensively evaluating its sealing strength. In actual testing, each performance is tested independently, which not only increases the complexity of the test procedure, but also reduces the accuracy of the test results. This is because it is known from the above analysis that the hot-pressed sealed components are in a high-temperature corrosive melt composed of sodium tetrachloroaluminate (NaAlCl4) during the test, and will be subject to the stress of the solid-liquid transformation process of NaAlCl4. Therefore, a single independent test of each performance cannot fully or accurately reflect the performance status of the hot-pressed sealed components in a high-temperature corrosive environment.
[0005] Therefore, based on the above analysis, the present application designs a life test method for hot pressing sealing components for sodium salt batteries. Summary of the invention
[0006] The purpose of the present invention is to provide a life test method for a hot-pressing sealing component for a sodium salt battery, so as to solve the shortcomings of the existing hot-pressing sealing component test method, such as low test accuracy and complicated test procedures.
[0007] The present invention provides a life test method for a hot pressing sealing component for a sodium salt battery, comprising the following steps:
[0008] S1. Adding a test sample into a preset sample container and sealing the sample container, wherein the test sample comprises a hot-pressed sealed component sample and solid sodium tetrachloroaluminate;
[0009] S2, placing the sealed sample container in a heating furnace and keeping it at a target temperature of 295-305° C. for 1-1.5 hours;
[0010] S3, cooling the sample container to room temperature;
[0011] S4, repeat the above steps S2 and S3 5-20 times;
[0012] S5. Open the sample container and take out the hot-pressing sealed component sample, rinse the hot-pressing sealed component with clean water to remove residual sodium tetrachloroaluminate and dry it;
[0013] S6. Perform helium inspection and tensile strength test on the hot-pressing sealing component sample to determine whether it meets the requirements.
[0014] As the preferred solution of this application:
[0015] In step S1, the amount of solid sodium tetrachloroaluminate added is based on the amount of liquid after melting that can immerse the hot-pressing sealing component sample.
[0016] As the preferred solution of this application:
[0017] Before S1, 8-10 heat-pressing and sealing components on the same tool are selected as a sample group, and heat-pressing and sealing components located at adjacent positions of the heat-pressing and sealing component samples in the sample group on the same tool are selected as a comparison group.
[0018] As the preferred solution of this application:
[0019] In S1, the sample container is a hollow columnar structure, and its constituent material is at least one of low carbon steel, stainless steel, Hastelloy or pure nickel.
[0020] As the preferred solution of this application:
[0021] In step S2, the sample container is placed in a heating furnace and gradually heated to a target temperature of 295-305°C at a heating rate of 0.5-1.5°C / min and then kept warm.
[0022] As the preferred solution of this application:
[0023] In step S3, the sample container is cooled at room temperature, which specifically includes: taking the sample container out of the heating furnace and cooling it at room temperature.
[0024] As the preferred solution of this application:
[0025] In step S5, after the sample container is opened, hot water at 80-100° C. is poured into the sample container to allow the sodium tetrachloroaluminate to react completely, and then the hot-pressed sealed component sample is taken out.
[0026] As the preferred solution of this application:
[0027] In step S6, the hot press sealing component sample is first subjected to helium testing, and then a tensile testing machine is used to test the bonding strength between the metallization layer and the nickel ring in the hot press sealing component sample to reflect the current sealing strength of the hot press sealing component sample. When the obtained test results meet the following requirements: the helium leakage rate is less than 1×10 -10 Pa.m3 / s, when the minimum sealing strength is greater than 1100N and there is no abnormality in the bare board of the sealing section, it means that the requirements are met.
[0028] Compared with the prior art, the advantages of this application are:
[0029] The present application first places the hot-pressed sealing component in a high-temperature corrosion environment composed of sodium tetrachloroaluminate (NaAlCl4), and repeatedly freezes and thaws it multiple times to accelerate the feedback of the mechanical decay of the hot-pressed sealing component in the battery service environment, and finally judges the sealing strength performance of the sealing component by testing the sealing strength and the helium leak rate. It can be seen that the method of the present application can simulate the real environment of the hot-pressed sealing component in the battery, so that the performance test of the hot-pressed sealing component is not only carried out on the basis of the high-temperature corrosion environment, but also takes into account the effects of the high-temperature corrosion environment and the stress in the solid-liquid transformation process of NaAlCl4 on the hot-pressed sealing component, which effectively improves the test accuracy, thereby improving the life and quality of the battery. Moreover, there is no need to test the high temperature resistance and corrosion resistance of the hot-pressed sealing component separately, which simplifies the traditional testing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the overall structure of the heat-pressing sealing assembly provided in the background technology of an embodiment of the present invention.
[0031] Figure 2 Weibull trend diagram of the comparison group and the test group provided in the embodiment of the present invention. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below in conjunction with specific implementations and with reference to the accompanying drawings. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.
[0033] This embodiment provides a life test method for a hot-pressing sealing assembly for a sodium salt battery, the method comprising the following steps:
[0034] S1. Add a test sample into a preset sample container and seal the sample container. The test sample comprises a hot pressing sealed component sample and solid sodium tetrachloroaluminate. The amount of solid sodium tetrachloroaluminate added is based on the amount of the melted liquid that can immerse the hot pressing sealed component sample. The solid sodium tetrachloroaluminate can be first heated to a molten state and added to the sample container, and then sealed after cooling.
[0035] In this step, the sample container is a pre-prepared container for the test sample. In this embodiment, the sample container is preferably a hollow cylindrical structure, and its constituent material is at least one of low carbon steel, stainless steel, Hastelloy or pure nickel. The sample container made of the above materials has strong corrosion resistance and heat transfer performance, and can meet the high temperature treatment of the test sample;
[0036] Meanwhile, in this step, the hot press sealing component samples are 8-10 samples selected from the same tooling, and the 8-10 samples constitute a sample group, and each sample is located at a different loading position of the tooling, so that not only the test accuracy of the hot press sealing component can be improved, but also different positions of the same tooling can be tested to realize the monitoring of the working state of the tooling. In addition, in order to detect the accuracy of the test, the hot press sealing components located at adjacent positions of the same tooling as the hot press sealing component samples in the sample group are selected as the comparison group, and the accuracy of the test method is judged by comparing the comparison group with the sample group;
[0037] S2, placing the sealed sample container in a heating furnace at 295-305° C. for 1-1.5 hours;
[0038] Specifically, this step is used to heat the test sample. In this embodiment, a heating furnace is preferably used for heating. The heating furnace is a graphite crucible cavity, and the maximum heating temperature can reach about 1000°C.
[0039] In this step, the heating furnace is initially at room temperature, the sample container is placed in the heating furnace, and gradually heated to a target temperature of 295-305°C at a heating rate of 0.5-1.5°C / min and then kept warm;
[0040] In this embodiment, the target temperature of the heating furnace is preferably about 300° C. (this temperature is used to simulate the working temperature environment of the sodium salt battery), and the sample container containing the test sample is placed in the heating furnace for insulation, and the insulation time is preferably 1 hour.
[0041] S3, taking the sample container out of the heating furnace and cooling it to room temperature; this step is used to cool the sample container, that is, the test sample, and the cooling method is preferably room temperature cooling. Of course, low temperature cooling can also be used when necessary.
[0042] S4, repeat the above steps S2 and S3 5-20 times;
[0043] This step is used to repeat the freeze-thaw operation, and the repetition frequency is preferably 5 times in this embodiment.
[0044] S5. Open the sample container and take out the hot-pressing sealed component sample, rinse the hot-pressing sealed component with clean water to remove residual sodium tetrachloroaluminate and dry it;
[0045] This step is used to process the hot-pressed sealed component samples after multiple freeze-thaw cycles. In this step, after the sample container is opened, hot water at 80-100°C can be repeatedly poured into the sample container to allow the sodium tetrachloroaluminate to react completely before the hot-pressed sealed component sample is taken out, thereby reducing the residual amount of sodium tetrachloroaluminate on the hot-pressed sealed component sample. In this embodiment, the rinsed sodium tetrachloroaluminate can be dried at room temperature or heated to dry, and this embodiment preferably uses room temperature drying.
[0046] S6, performing helium inspection and tensile strength test on the hot pressing sealing component sample to determine whether it meets the requirements;
[0047] Specifically, after the hot-pressed sealed component samples are qualified by helium inspection, the sealing strength of the sealed component samples is tested by a tensile testing machine through the test fixture. The sealing strength mainly refers to the strength of the inner nickel ring and the outer nickel ring on the hot-pressed sealed component, that is, the sealing strength or bonding integrity of the ceramic metallization layer and the nickel ring. According to actual conditions, the hot-pressed sealed components of normal quality should meet the following requirements after multiple freeze-thaw treatments: the helium leakage rate is less than 1×10 -10 Pa.m3 / s, when the minimum sealing strength is greater than 1100N and there is no abnormality in the bare board of the sealing section, it means that the requirements are met.
[0048] See Table 1, which is a comparison chart of helium inspection and sealing strength of the hot-pressed sealing component samples (test group) treated by the life test method of the hot-pressed sealing component for sodium salt batteries described above in this embodiment and the hot-pressed sealing components (comparison group) obtained by the traditional method:
[0049] Table 1
[0050]
[0051]
[0052] In this embodiment, the number of hot press sealing component samples in the test group in the above table is preferably 8, and each hot press sealing component in the comparison group includes a hot press sealing component adjacent to the loading position of each hot press sealing component sample in the test group, that is, a hot press sealing component sample in one test group corresponds to a hot press sealing component in the comparison group; and each hot press sealing component in the test group and the comparison group are normal hot press sealing components.
[0053] According to the comparison in the above table, the strength of the inner and outer nickel rings in the test group is significantly reduced compared with the control group, and the helium leakage rate is less than 1×10 -10 Pa.m3 / s, and the sealing strength is greater than 1100N. This proves that, compared with the existing traditional testing methods, the sealing strength parameters of the hot pressing sealing assembly tested by the method in this embodiment are more accurate.
[0054] like Figure 2 As shown in FIG. 1 , it is a Weibull trend diagram of the comparison group and the test group provided in this embodiment. Through the Weibull analysis of the sealing strength degradation trend, it can be seen that the sealing strength of each hot-pressing sealing component in the test group is less than the sealing strength of the hot-pressing sealing component in the comparison group at the adjacent loading position, and the helium leakage rate and sealing strength of each sealing component in the test group are within the normal range, that is, the helium leakage rate is less than 1×10 -10 Pa.m3 / s, the sealing strength is greater than 1100N; the Weibull trend diagram further proves that the sealing strength parameters of the hot pressing sealing assembly tested by the method in this embodiment are more accurate.
[0055] In summary, the present embodiment places the hot-pressed sealing component in sodium tetrachloroaluminate and uses multiple freeze-thaw cycles to achieve accelerated simulation of the working environment of the hot-pressed sealing component in the battery. That is, the testing process of the present embodiment is not only carried out on the basis of a high-temperature corrosion environment, but also takes into account the effects of the high-temperature corrosion environment and the stress in the solid-liquid transformation process of NaAlCl4 on the hot-pressed sealing component. On the one hand, the testing accuracy and efficiency of the hot-pressed sealing component are improved, thereby improving the service life and quality of the battery. At the same time, the present embodiment uses multiple freeze-thaw cycles in a sodium tetrachloroaluminate environment to conduct tests to evaluate the sealing strength. Compared with the traditional method, it effectively simplifies the process flow, saves process costs, and improves the testing rate.
[0056] The above is only an embodiment of the present invention, and the common knowledge such as the known specific structure and characteristics in the scheme is not described in detail here. It should be pointed out that for those skilled in the art, several improvements can be made without departing from the present invention, which should also be regarded as the protection scope of the present invention, and these will not affect the effect of the implementation of the present invention and the practicality of the patent. The scope of protection required by this application shall be based on the content of the claims, and the specific implementation methods and other records in the specification can be used to interpret the content of the claims.
Claims
1. A life test method for a hot-pressing sealing assembly for a sodium salt battery, characterized in that: The following steps are included: S1. Adding a test sample into a preset sample container and sealing the sample container, wherein the test sample comprises a hot-pressed sealed component sample and solid sodium tetrachloroaluminate; S2, placing the sealed sample container in a heating furnace and keeping it at a target temperature of 295-305° C. for 1-1.5 hours; S3, cooling the sample container to room temperature; S4, repeat the above steps S2 and S3 5-20 times; S5. Open the sample container and take out the hot-pressing sealed component sample, rinse the hot-pressing sealed component with clean water to remove residual sodium tetrachloroaluminate and dry it; S6. Perform helium inspection and tensile strength test on the hot-pressing sealing component sample to determine whether it meets the requirements.
2. The life test method of the hot-pressing sealing assembly for sodium salt batteries according to claim 1, characterized in that: In step S1, the amount of solid sodium tetrachloroaluminate added is based on the amount of liquid after melting that can immerse the hot-pressing sealing component sample.
3. The life test method of the hot-pressing sealing assembly for sodium salt battery according to claim 1, characterized in that: Before S1, 8-10 heat-pressing and sealing components on the same tool are selected as a sample group, and heat-pressing and sealing components located at adjacent positions of the heat-pressing and sealing component samples in the sample group on the same tool are selected as a comparison group.
4. The life test method of the hot-pressing sealing assembly for sodium salt battery according to claim 1, characterized in that: In S1, the sample container is a hollow columnar structure, and its constituent material is at least one of low carbon steel, stainless steel, Hastelloy or pure nickel.
5. The life test method of the hot-pressing sealing assembly for sodium salt battery according to claim 1, characterized in that: In step S2, the sample container is placed in a heating furnace and gradually heated to a target temperature of 295-305°C at a heating rate of 0.5-1.5°C / min and then kept warm.
6. The life test method of the hot-pressing sealing assembly for sodium salt battery according to claim 1, characterized in that: In step S3, the sample container is cooled at room temperature, which specifically includes: taking the sample container out of the heating furnace and cooling it at room temperature.
7. The life test method of the hot-pressing sealing assembly for sodium salt battery according to claim 1, characterized in that: In step S5, after the sample container is opened, hot water at 80-100° C. is poured into the sample container to allow the sodium tetrachloroaluminate to react completely, and then the hot-pressed sealed component sample is taken out.
8. The life test method of the hot-pressing sealing assembly for sodium salt battery according to claim 1, characterized in that: In step S6, the hot press sealing component sample is first subjected to helium testing, and then a tensile testing machine is used to test the bonding strength between the metallization layer and the nickel ring in the hot press sealing component sample to reflect the current sealing strength of the hot press sealing component sample. When the obtained test results meet the following requirements: the helium leakage rate is less than 1×10 -10 Pa.m3 / s, when the minimum sealing strength is greater than 1100N and there is no abnormality in the bare board of the sealing section, it means that the requirements are met.